Golden ratio: A subtle regulator in our body and cardiovascular system?. (15th November 2016) - Ozturk, Selcuk; Yalta, Kenan; Yetkin, Ertan
Abstract: Golden ratio, which is an irrational number and also named as the Greek letter Phi (φ), is defined as the ratio between two lines of unequal length, where the ratio of the lengths of the shorter to the longer is the same as the ratio between the lengths of the longer and the sum of the lengths. The so-called formula is a mathematical ratio and there exist a variety of examples in natural and man-made structures of great beauty. Moreover, golden ratio is expressed throughout the human body in some ways, including digits, uterus, teeth, and cardiovascular system. Although the association of Fibonacci series or golden ratio with systems and organs of human being has not been assessed in depth yet, the mainstream regulation of cardiovascular system seems to be associated with golden ratio. This raises the idea that there might have been a fine and subtle regulator in our body. In this article, we aimed to elaborate the relationship between the existence of golden ratio and the human body and to discuss the golden ratio and its association with cardiovascular system. Highlights: There is a propensity for golden ratio to appear in the nature This ratio provides minimizing of the wasted space. The need for energy and nutrients are optimized in golden ratio. Our heart is beating and pumping in golden ratio. The harmony in our body and cardiovascular system seem to be regulated by subtle forces.